Aloïs Riegl and the riddle of Rembrandt’s Staalmeesters: Vienna schooling Dutch art scholarship - Benjamin Binstock (Journal of Art Historiography, 2023)
Aloïs Riegl’s elucidations of visual particulars in his Dutch Group Portrait of 1902 are not in contrast to but rather inform his theory of the development of group portraiture. Riegl sought to explain the Kunstwollen or ‘will of art’ of Dutch group portraits, what they seek to do as art. Despite his errors, his approach is applicable to current interpretations, above all the riddle of Rembrandt’s Staalmeesters, and can thus serve, in a cumulative art historiography, as a means of ‘Vienna schooling’ Dutch art scholarship. Building on Riegl’s analysis, this paper proposes that after reaching an impasse in both his group sketch for and first painted composition of his Staalmeesters, Rembrandt made portrait studies of two sample masters in their account book, and revised his composition to show them responding to his drawings and looking out at him. He thereby embedded portraiture (Riegl’s ‘external unity’) at the heart of his narrative (‘internal unity’). As in his earlier group portraits, he displaced speech by sight and text by image, achieving what Riegl identified as his goal of interfusing the psyches or souls of the figures and the beholder, making them part of a moving, seeing, thinking whole. Rembrandt reflected on the development of his tradition and his own paintings, making his task in the process of portraiture into the subject of his painting, and thereby redeemed his relation to his tradition.